A "Research" Database on Infrastructure Economic Performance - Estache, Antonio; Goicoechea, Ana (World Bank, Washington, DC, 2012)
The authors present an infrastructure database that was assembled from multiple sources. Its main purposes are: (1) to provide a snapshot of the sector as of the end of 2004; and (2) to facilitate quantitative analytical research on infrastructure. The paper includes definitions, source information, and the most recent data available for 37 performance indicators that proxy access, affordability, and quality of service. Additionally, the database includes a snapshot of 15 reform indicators across infrastructure sectors.